Stress indicators, immunity, and performance of quail fed on the basil leaf meal waste during the growth period - Ikhwanda, K.; Ulupi, N.; Maheshwari, H.; Wahyuni, W. (Journal of the Indonesian Tropical Animal Agriculture, 2026)
This study aimed to evaluate the effects of adding basil (Ocimum basilicum L.) leaf meal waste to feed on stress indicators, immune responses, and performance of growing quails (Coturnix coturnix japonica). Two hundred female quails 3-week-old were allocated in a completely randomized design with four treatments: 0% (P0), 1.5% (P1), 3% (P2), and 4.5% (P3), each with five replicates of 10 birds. The Observed variables included oxygen saturation, heterophil/lymphocyte ratio, hepatic superoxide dismutase (SOD) activity and malondialdehyde (MDA) level, leukocyte profiles, and clearance ability against Salmonella pullorum. Growth performance was measured through feed intake, body weight gain, and feed conversion ratio. Results showed that 3% basil leaf meal waste improved oxygen saturation and SOD activity, reduced H/L ratio and MDA level, and produced the highest bacterial killing ability. The best growth performance and most efficient feed conversion were also observed in P2. It can be concluded that 3% inclusion effectively reduces oxidative stress, enhances immunity, and improves quail performance.